1996
DOI: 10.1128/aac.40.1.274
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and pharmacokinetics of four new 7-azetidinyl fluoroquinolones

Abstract: The activity of E-4535, E-4534, E-4528, and E-4527, four new 7-azetidinyl-6-fluoroquinolones, was studied to evaluate the role played by the C-2' and C-3' substitutions of the azetidinyl group, together with a C-8 fluorine atom. In general, like other 6,8-difluoroquinolones, E-4534 and E-4527 showed higher levels of activity than the corresponding monofluorinated derivatives, E-4535 and E-4528. E-4535 and E-4534, having a 7-(2-methyl-3-aminoazetidinyl) substituent, demonstrated higher levels of activity in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…A computational approach indicated that C-8 fluorine or alkoxy groups, when coupled with an N-1 cyclopropyl moiety, would increase bacteriostatic activity (15). This was the case for 15 of 16 bacterial species subsequently tested (4). Another study showed that a C-8 chlorine increased activity against Pseudomonas aeruginosa, especially with strains containing a quinolone-resistant gyrase (14).…”
mentioning
confidence: 99%
“…A computational approach indicated that C-8 fluorine or alkoxy groups, when coupled with an N-1 cyclopropyl moiety, would increase bacteriostatic activity (15). This was the case for 15 of 16 bacterial species subsequently tested (4). Another study showed that a C-8 chlorine increased activity against Pseudomonas aeruginosa, especially with strains containing a quinolone-resistant gyrase (14).…”
mentioning
confidence: 99%
“…15 Un caso especial lo constituye grepafloxacina (OPC 17116) antimicrobiano recientemente retirado del mercado farmaceútico por fenómenos de cardiotoxicidad derivados de su uso. 26 Otras quinolonas con ciclopropil como sustituyente en N1 son balofloxacina (Q-35) (también discontinuada), 27 CS-940, 28 las quinolonas desarrolladas por Laboratorios Esteve de España E-3846, 29 E-4884, E-4874, 30 E-4502, E-4501, E-4500, E-4474, E-4480, E-4441, 31 E-4695, 32 E-4535, E-4527, E-4528, E-4534, 33 E-5065, 34 gatifloxacina (AM 1155, CG 5501), 35 AM-1091, 36 A-60919, 15 CI-990, PD 131112, 22 CI-938, 15 moxifloxacina (BAY 12-8039), 16 MF 5137, 16 sitafloxacina (DU-6859a). 37 El ciclopropil combina favorables propiedades estéricas, espaciales y de interacción electrónica, así la quinolona de mayor uso clínico, ciprofloxacina, presenta un grupo ciclopropil a nivel N1, exhibiendo una potente actividad sobre enterobacterias y Pseudomonas aeruginosa.…”
Section: Posiciónunclassified
“…11 La presencia de un grupo azetidina en la posición 7 tiene resultados variables en la actividad del antimicrobiano, así las moléculas más pequeñas y por tanto con menos sustituyentes exhiben una modesta actividad comparada con ciprofloxacina, mientras que moléculas mayores presentan una actividad comparable e incluso superior a la de ciprofloxacina, particularmente sobre especies Gram positivas. [29][30][31][32][33][34]42…”
Section: Posiciónunclassified
“…It has an identical activity to ciprofloxacin against Enterobacteriaceae, and is slightly more active than levofloxacin. It is less active than ciprofloxacin against P. aeruginosa (Table 11) [36]. In vivo, in systemic infections, it is more active than ciprofloxacin against S. aureus HS-93, E. coli HM 42 and P. aeruginosa HS-46.…”
Section: E 4534mentioning
confidence: 99%